Efficacy of SGLT2 inhibitors in IgA nephropathy associated with alcoholic liver cirrhosis accompanied by nephrotic syndrome: a case report - Yoshimura, Yusuke; Ikuma, Daisuke; Mizuno, Hiroki; Kono, Kei; Kinowaki, Keiichi; Sugimoto, Hisashi; Kamido, Hisashi; Sawada, Yuichiro; Mizuta, Masato; Kurihara, Shigekazu; Oba, Yuki; Yamanouchi, Masayuki; et al. (Frontiers in Nephrology, 2024)
We present a 51-year-old male patient with a history of Child-Pugh Grade B alcoholic liver cirrhosis (ALC) who developed renal impairment (serum creatinine of 2.00 mg/dL) and nephrotic syndrome (a urinary protein level of 4.35 g/gCr). The patient was diagnosed with immunoglobulin A nephropathy (IgAN) associated with ALC based on findings from comprehensive evaluations, including markedly elevated serum IgA levels (883.7 mg/dL), a kidney biopsy revealing significant IgA deposition in the para-mesangial area, and a liver diagnosis showing long-standing advanced ALC. Our treatment approach involved initiating dapagliflozin therapy, an SGLT2 inhibitor, alongside strict alcohol abstinence. Remarkably, the patient demonstrated a dramatic reduction in proteinuria within one week of dapagliflozin administration. No hypoglycemic events were observed. This case adds valuable clinical insights into the potential therapeutic role of SGLT2 inhibitors in IgAN associated with ALC. Specifically, in cases where conventional steroid therapies may be contraindicated due to coexisting comorbidities such as diabetes or obesity, dapagliflozin emerges as a potentially efficacious alternative. Further investigations are warranted to validate these preliminary observations.